Implementasi Jaringan Syaraf Tiruan Dengan Multilayer Perceptron Untuk Analisa Pemberian Kredit - Amrin, Amrin; Satriadi, Irawan (JURIKOM (Jurnal Riset Komputer), 2018)
The Problem that is often faced in giving credit is determining the decision to give credit to  someone, while other issues are not all credit payments can run well. Among the causes are errors of judgment in making credit decisions. In this study will be used  neural network with multilayer perceptron method to analyze the feasibility of giving credit. From the test results to measure the performance of the method is to use testing methods confusion matrix and ROC curve, it is known that the method of  neural network multilayer perceptron has a value of  96,1% accuracy and AUC value of  0.999. This shows that the model produced, including the classification is Exellent Clasification because it has the AUC values between 0.90- 1.00.